The food and beverage cues in digital marketing model: special considerations of social media, gaming, and livestreaming environments for food marketing and eating behavior research - Maksi, Sara J.; Keller, Kathleen L.; Dardis, Frank; Vecchi, Martina; Freeman, Jason; Evans, Rebecca K.; Boyland, Emma; Masterson, Travis D. (Frontiers in Nutrition, 2024)
Digital marketing to children, teens, and adults contributes to substantial exposure to cues and persuasive messages that drive the overconsumption of energy dense foods and sugary beverages. Previous food marketing research has focused on traditional media, but less is known about how marketing techniques translate within digital platforms, such as social media, livestreaming, and gaming. Building upon previous theories and models, we propose a new model entitled Food and Beverage Cues in Digital Marketing (FBCDM). The FBCDM model specifies key marking elements and marketing integration strategies that are common on digital platforms and are hypothesized to enhance the effects of advertising and incentive sensitization process. FBCDM also categorizes measurable outcomes into three domains that include brand, food, and social outcomes. Additionally, repeated marketing exposure and the resulting outcomes are hypothesized to have long term consequences related to consumer markets, consumption behavior, culture, and health. We include a discussion of what is currently known about digital marketing exposure within the outcome domains, and we highlight gaps in research including the long-term consequences of digital marketing exposure.The FBCDM model provides a conceptual framework to guide future research to examine the digital marketing of food and beverages to children and adolescents in order to inform government and industry policies that restrict the aggressive marketing of products associated with obesity and adverse diet related outcomes.